The Municipal Register, Containing the City Charter, with Rules and Orders of the City Council, Also the Ordinances, and a List of the Officers of the City of Roxbury, for 1848-49, at 58 (1848) - (:unkn) unknown (My University, 1848)
An Ordinance To prevent unlawful and injurious practices in the streets and other public places in the city: Prohibited the discharge of any firearms within the city of Roxbury
Keywords: DISCHARGE